P178 EFFICACY OF FECAL MICROBIOTA TRANSPLANTATION FOR RECURRENT C. DIFFICILE INFECTION IN INFLAMMATORY BOWEL DISEASE. (18th January 2018) - Tariq, Raseen; Disbrow, Molly B; DiBaise, John; Orenstein, Robert; Loftus, Edward V; Pardi, Darrell S; Khanna, Sahil
Abstract: Background: C. difficile infection (CDI) in Inflammatory bowel disease (IBD) is associated with poor outcomes. Fecal microbiota transplantation (FMT) is highly effective for recurrent CDI but data on outcomes of FMT for management of IBD are lacking. We report outcomes of FMT in adults with CDI and IBD. Methods: Adult patients with IBD and recurrent or non-resolving CDI who had failed oral treatment for CDI underwent FMT after stopping CDI treatment 24 hours prior to FMT. Outcomes were assessed by patient symptoms and stool tests for unresolved symptoms. Results: There were 145 patients (36.5% Crohn's, 61.3% UC, 3% indeterminate colitis; 51.7%% female) with median age 46 yrs, median IBD duration 8 yrs (range 0–47). Median CDI episodes were 3 (range 1–20) and 61.6% patients failed prolonged vancomycin tapers. For IBD, 37.9% were on 5-ASA, 39.3% on steroids, 38.6% on biologics and 24.8% on immunomodulators. Overall 35.8% had an IBD flare at the time of FMT. Post-FMT, 33.1% (n=48) had symptom improvement with diarrhea resolution, 65.5% (n=95) underwent CDI testing due to ongoing diarrhea and 20% (29/145) tested positive upon a median follow up 9.3 months (range 0.1–51), for an overall success rate of 80%. Failures were treated with antibiotics alone (18/29) or repeat FMT (11/29). Post-FMT, 35.8% had an ongoing flare, 29% had worsening IBD symptoms and needed IBD therapy escalation after CDI resolution. None were able discontinue IBD therapy after FMT. CDI history (3 or more prior CDI episodes, number of metronidazole or vancomycin courses, IBD type, steroids, ASA, immunomodulators or biologics use, presence of IBD flare at the time or after FMT were not associated with failure of FMT for CDI. Conclusions: FMT is safe and effective mode of treatment of recurrent CDI in patients with IBD. However, FMT does not improve the course of IBD but allows planned escalation of IBD therapy after CDI resolution.